An Evaluation of Wikipedia as a Resource for Patient Education in Nephrology. Issue 2 (22nd February 2013) - Thomas, Garry R.; Eng, Lawson; de Wolff, Jacob F.; Grover, Samir C.
Abstract Wikipedia, a multilingual online encyclopedia, is a common starting point for patient medical searches. As its articles can be authored and edited by anyone worldwide, the credibility of the medical content of Wikipedia has been openly questioned. Wikipedia medical articles have also been criticized as too advanced for the general public. This study assesses the comprehensiveness, reliability, and readability of nephrology articles on Wikipedia. The International Statistical Classification of Diseases and Related problems, 10th Edition (ICD‐10) diagnostic codes for nephrology (N00–N29.8) were used as a topic list to investigate the English Wikipedia database. Comprehensiveness was assessed by the proportion of ICD‐10 codes that had corresponding articles. Reliability was measured by both the number of references per article and proportion of references from substantiated sources. Finally, readability was assessed using three validated indices (Flesch‐Kincaid grade level, Automated readability index, and Flesch reading ease). Nephrology articles on Wikipedia were relatively comprehensive, with 70.5% of ICD‐10 codes being represented. The articles were fairly reliable, with 7.1 ± 9.8 (mean ± SD) references per article, of which 59.7 ± 35.0% were substantiated references. Finally, all three readability indices determined that nephrology articles are written at a college level. Wikipedia is a comprehensive and fairly reliable medical resource for nephrology patients that is written at a college reading level. Accessibility of this information for the general public may be improved by hosting it at alternative Wikipedias targeted at a lower reading level, such as the Simple English Wikipedia.